2019
DOI: 10.1038/s41598-019-51023-0
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of positive and negative symptoms through the illness course: an fMRI study in early psychosis and chronic schizophrenia

Abstract: Psychotic illness is associated with cognitive control deficits and abnormal recruitment of neural circuits subserving cognitive control. It is unclear to what extent this dysfunction underlies the development and/or maintenance of positive and negative symptoms typically observed in schizophrenia. In this study we compared fMRI activation on a standard Stroop task and its relationship with positive and negative symptoms in early psychosis (EP, N = 88) and chronic schizophrenia (CHR-SZ, N = 38) patients. CHR-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 75 publications
1
29
0
1
Order By: Relevance
“…Rather importantly, our results indicate that the impact of genetic variation potentially regulating FXR1-GSK3β signaling on psychopathology of SCZ is quite specific for NSs, whereas it is not significant for positive symptoms. One possible explanation of such a finding is that, since there is evidence that SCZ negative and positive symptom domains are supported by different neurobiological and brain circuitry systems [70,71], it is possible that genetic variation impacting on one of the two domains has less pronounced effects on the other one. This seems particularly plausible in light of existing evidence that genomic variation associated with SCZ at genome-wide level of significance clusters to different biological ontologies that distinctly support either positive or NSs [46].…”
Section: Discussionmentioning
confidence: 99%
“…Rather importantly, our results indicate that the impact of genetic variation potentially regulating FXR1-GSK3β signaling on psychopathology of SCZ is quite specific for NSs, whereas it is not significant for positive symptoms. One possible explanation of such a finding is that, since there is evidence that SCZ negative and positive symptom domains are supported by different neurobiological and brain circuitry systems [70,71], it is possible that genetic variation impacting on one of the two domains has less pronounced effects on the other one. This seems particularly plausible in light of existing evidence that genomic variation associated with SCZ at genome-wide level of significance clusters to different biological ontologies that distinctly support either positive or NSs [46].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the finding of an association between cerebellar morphology and p-factor in younger ( Romer et al, 2018 ) but not older ( Romer et al, 2019 ) adults might also reflect a dynamic role of the cerebellum throughout the lifespan, where contributions of cerebellar structure to psychopathology are greater at a younger age. ( Vanes et al, 2019 )Finally, a correlation between reduced visual association cortex volume and the p -factor might reflect less efficient integration of bottom-up sensory signals with top-down executive control processes associated with a greater burden of psychopathology.…”
Section: The Dimensional Approach: Neuroimaging Studies Of General Psmentioning
confidence: 99%
“…The limited prior work on predicting schizophrenia symptoms via machine learning has thus far only been performed on the basis of composite symptoms (10,11), general functioning (12,13) and polygenic risk scores for schizophrenia (14). Other neuroimaging studies have also reported univariate correlates (15,16), or lack thereof (17,18), with symptom severity on the basis of composite summary scores rather than those of the underlying symptoms, an approach which significantly comprises aetiological specificity (19). For example, if we were to compare two patients, one with disorganised thought processes which render them unable to bathe themselves to another with severe alogia who is unable to communicate, these are vastly different symptoms which in turn are likely to be caused by different sources of dysfunction in different neural networks.…”
Section: Introductionmentioning
confidence: 99%